The life span-prolonging effect of sirtuin-1 is mediated by autophagy - Morselli, E.; Maiuri, M. C.; Markaki, M.; Megalou, E.; Pasparaki, A.; Palikaras, K.; Criollo, A.; Galluzzi, L.; Malik, S. A.; Vitale, I.; Michaud, M.; Madeo, F.; et al. (Autophagy, 2010)
The life span of various model organisms can be extended by caloric restriction as well as by autophagy-inducing pharmacological agents. Life span-prolonging effects have also been observed in yeast cells, nematodes and flies upon the overexpression of the deacetylase Sirtuin-1. Intrigued by these observations and by the established link between caloric restriction and Sirtuin-1 activation, we decided to investigate the putative implication of Sirtuin-1 in the response of human cancer cells and Caenorhabditis elegans to multiple triggers of autophagy. Our data indicate that the activation of Sirtuin-1 (by the pharmacological agent resveratrol and/or genetic means) per se ignites autophagy, and that Sirtuin-1 is required for the autophagic response to nutrient deprivation, in both human and nematode cells, but not for autophagy triggered by downstream signals such as the inhibition of mTOR or p53. Since the life spanextending effects of Sirtuin-1 activators are lost in autophagy-deficient C. elegans, our results suggest that caloric restriction and resveratrol extend longevity, at least in experimental settings, by activating autophagy.
Keywords: Aging/drug effects/*genetics; Animals; Animals, Genetically Modified; Autophagy/drug effects/genetics/*physiology; Caenorhabditis elegans/genetics/physiology; Enzyme Activation/drug effects; Humans; Models, Biological; Sirtuin 1/genetics/metabolism/*physiology